A primer for power quality testing & inspection (Power quality)
This program introduces the hands-on part of power quality work. It covers what test equipment to use, how it works and where to use it. It also shows how the Code applies to the requirements of sensitive electronic equipment, as well as the typical problem spots and how to identify them with measurements and observations.